An integrated approach to understand territory dynamics: The Coastal Alentejo (Portugal) - Nelson Lourenço; Carlos Russo Machado; Maria do Rosário Jorge; Luís Rodrigues (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper aims at presenting an integrated framework for the study of territorial dynamics in coastal areas. The use of Geographic Information Systems made possible the association of land cover data and socio-economic data using different levels of spatial analysis. The Coastal Alentejo (Portugal) was used as case study to identify these territorial dynamics. Being land cover and land use changes one of the main issues integrating the large debate on sustainable development, its analysis demand clearly an integration of spatial /landscape data with the socio-economic data, which has been recently widely recognised. The question is how this integration is possible, and how can it best be achieved to understand the change. Moreover, the land use changes studies must be a contextualised analysis centred in the individual inside the context where he acts. This departing point assumes that the individual induces land use changes but he also reflects these changes, which were made by him or by other agents that intervene, directly or indirectly, in the land use. Thus we must consider and analyse the impact of external driving forces such as the national and international policies and regulations, being necessary, therefore, an effort to make this kind of analysis at Regional, Local and Individual Level.The coastal areas are special focus given the increasing importance that they had assumed in the global frame of the present economic development. The number and diversity of agents that are searching for space in coastal areas increases the needs for an integrated management in a way to minimise the negative impacts of the increasing number of activities conflicting in these areas. The nature and distribution of human activities on coastal areas result from the action of a range of driving forces Œ demographic, institutional, commercial and market, cultural and technological. The impact of these forces explains the land use changes and the way in which the coastal resources are affected.Toward the identification and understanding the environmental problems of coastal areas it is important, therefore, to analyse the efficacy of the administrative structures at the level of the formulation of the legislative frame and its practice giving possible to understand the articulation, at distinct levels of the institutional dimensions. Moreover the institutional frame, given the integration of Portugal in the European Union since the middle eighties, is in part the reflection of the problems and needs, which are perceived also at the international level. In Portugal the responsibility of management of coastal resources is distributed by several administrative structures that intervene at different spatial levels (national, regional and local levels). This intervention present some contradictions caused by the different objectives of the planning tools, which frame those administrative structures.In what relates to the methodological design, this study is based in an integrated perspective that aims at understand the processes of land use change. The association of different scientific approaches and levels of analysis will accomplish this posture of integration. However, this multi-disciplinary integration cannot be faced as a superimposition or assembling of divers empirical approaches. It represents an articulation between the different scientific domains and levels of spatial or time analysis. The time analysis it is a significant element of the methodological design. If this studies aim at understand the processes of land use change, it is required to analyse different periods, besides the study of different rhythms or cycles of the phenomena. The accurate study of these different moments must contemplate the changes of the biophysical and social frames. The land use change is, therefore, the reflection of the practices of the different agents conditioned by the changes in the global frame of each period. In order to articulate these spatial and temporal levels of analysis of the georeferenced data it was implemented a GIS. How to articulate information from different sources and natures, different scales into the system of analysis is one of the main challenges of the work carried on.
Keywords: Q2; Q20; 330; Integrated analysis; coastal areas; land-use; agents of change; Bodennutzung; Informationssystem; Küstenregion; Alentejo